A Synthetic Chloride Channel Restores Chloride Conductance in Human Cystic Fibrosis Epithelial Cells - Shen, Bing; Li, Xiang; Wang, Fei; Yao, Xiaoqiang; Yang, Dan (PLOS ONE, 2012)
Mutations in the gene-encoding cystic fibrosis transmembrane conductance regulator (CFTR) cause defective transepithelial transport of chloride (Cl−) ions and fluid, thereby becoming responsible for the onset of cystic fibrosis (CF). One strategy to reduce the pathophysiology associated with CF is to increase Cl− transport through alternative pathways. In this paper, we demonstrate that a small synthetic molecule which forms Cl− channels to mediate Cl− transport across lipid bilayer membranes is capable of restoring Cl− permeability in human CF epithelial cells; as a result, it has the potential to become a lead compound for the treatment of human diseases associated with Cl− channel dysfunction.